2013
DOI: 10.1038/leu.2013.379
|View full text |Cite
|
Sign up to set email alerts
|

High hyperdiploidy among adolescents and adults with acute lymphoblastic leukaemia (ALL): cytogenetic features, clinical characteristics and outcome

Abstract: High hyperdiploidy (HeH, 51-65 chromosomes) is an established genetic subtype of acute lymphoblastic leukaemia (ALL). The clinical and cytogenetic features as well as outcome of HeH among adolescents and adults have not been thoroughly investigated. Among 1232 B-cell precursor ALL patients (15-65 years) treated in the UKALLXII/ECOG2993 trial, 160 (13%) had a HeH karyotype, including 80 patients aged >24 years. The frequency of HeH was the same in Philadelphia chromosome (Ph)-positive and -negative cases, but P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 27 publications
1
43
1
3
Order By: Relevance
“…Hyperdiploidy (47-57 chromosomes) which carry good prognosis was observed in 9 patients with B-cell phenotype. Its occurrence in younger age group (15-29 years) in this study is in accordance with the literature (Faderl et al, 2010;Chilton et al, 2013). The difference between 15-19 year and 20-29 year age group was not significant (p=1.0).…”
Section: Discussionsupporting
confidence: 81%
“…Hyperdiploidy (47-57 chromosomes) which carry good prognosis was observed in 9 patients with B-cell phenotype. Its occurrence in younger age group (15-29 years) in this study is in accordance with the literature (Faderl et al, 2010;Chilton et al, 2013). The difference between 15-19 year and 20-29 year age group was not significant (p=1.0).…”
Section: Discussionsupporting
confidence: 81%
“…9,12,13,15 The SNP array analysis identified three additional high hyperdiploid and five additional low hypodiploid cases, showing that this method is frequently more sensitive for detection of aneuploidy than conventional cytogenetic analysis. In line with high hyperdiploid childhood ALL and a recent cytogenetic study on high hyperdiploid adult cases, 16,17 the cases in this study showed frequent gains of chromosomes X, 4, 10, 17, 18 and 21, although the pattern of chromosomal gains was less specific than in pediatric ALL. All low hypodiploid cases had retained heterodisomy for chromosomes X and 21 and lost chromosomes 7 and 17, in line with previous reports.…”
Section: Discussionmentioning
confidence: 57%
“…We found that HeH was associated with favorable outcomes, even when +der(22)t(9;22) or −9/9p was also present. HeH has been well‐established to be associated with superior survival in adults with ALL, although most studies have primarily evaluated patients with Philadelphia chromosome‐negative disease . Our finding that the negative prognostic influence of +der(22)t(9;22) and −9/9p is restricted to patients without HeH highlights that HeH ALL is a unique clinical entity, including among patients with Ph+ ALL.…”
Section: Discussionmentioning
confidence: 86%